Is there a difference in the phthalate exposure between adults with metabolic disorders and healthy ones? - Stepanović Kristina; Vuković Bojan; Milanović Maja; Milošević Nataša; Bosić-Živanović Dragana; Stojadinović Aleksandra; Tomić-Naglić Dragana; Lepić Sanja; Milić Nataša; Medić-Stojanoska Milica (Vojnosanitetski Pregled, 2022)
Background/Aim. Phthalates are recognized as endocrine-disrupting compounds and are extensively present in a variety of everyday products. Chronic exposure to phthalates is suspected to be associated with a range of health disorders. The aim of the study was to examine the abundance of phthalate metabolites in the urine samples among adults in the Autonomous Province of Vojvodina, Serbia, and to determine the prevalence of phthalate metabolites in healthy individuals and those with metabolic disorders such as obesity and newly diagnosed type 2 diabetes mellitus (T2DM). Methods. For the study purpose, the first morning urine sample of 308 participants was screened for the presence of 10 phthalate metabolites: mono-ethyl phthalate (MEP), mono-(2-ethylhexyl) phthalate (MEHP), mono-n-butyl phthalate (MBP), mono-iso-allyl phthalate (MiAP), mono-n-allyl phthalate (MnAP), mono-cyclohexyl phthalate (MCHP), mono-benzyl phthalate (MBzP), mono-n-octyl phthalate (MOP), mono-n-propyl phthalate (MPP) and mono-methyl phthalate (MMP). Results. At least one phthalate metabolite was detected in the first morning urine sample in 50.32% of the examined population. The most frequently detected phthalate metabolites were MEP and MEHP. Out of all phthalate-positive participants, 38.3% of them had one, 10.7% had two, while 1.3% of participants had three phthalate metabolites in the first morning urine sample. A significant difference (p < 0.05) between groups was observed on MEP and MMP frequency, while border-line significant difference (p < 0.1) between groups was observed on MEHP and MCHP frequency. Conclusion. In the Vojvodina region, both healthy adults and those with metabolic disorders such as obesity and newly diagnosed T2DM are predominantly exposed to di-ethyl phthalate and di-(2-ethylhexyl)phthalate since MEP and MEHP were the most frequently detected phthalate metabolites. Further re-search is required in order to provide more details of the phthalates influence on the adverse health effects.